Synthesis, Structural, Spectroscopic, and DFT Characterization of a Thermodynamically Stable Bis(quercetin)copper(II) Complex and Its α-Amylase Inhibitory Activity - Puteri Khansa Salsabila; Yusi Deawati; Regaputra Satria Janitra; Safri Ishmayana; Iman Permana Maksum; Yessi Permana; Yudha Prawira Budiman (Journal of Multidisciplinary Applied Natural Science, 2026)
Quercetin (Q) is a dietary flavonol with promising antidiabetic activity but limited therapeutic utility due to poor solubility and low bioavailability. Herein, we report a temperature-controlled synthesis, structural characterization, and α-amylase inhibitory activity of a copper(II)–quercetin (CuQ) complex prepared from a 1:1 Cu(II):quercetin mixture in methanol at 65 °C. The characterization techniques include an elemental analysis (EA), AAS, TGA, MSB, UV-Vis, and FTIR. Elevated temperature predominantly affords a bis(quercetin)-Cu(II) complex, [Cu(H2O)(Q)2]·4H2O, supported by DFT calculations. Spectroscopic, thermal, and magnetic data are consistent with a proposed mononuclear Cu(II) structure, in which the metal center is coordinated by two quercetin ligands. DFT calculations suggest a thermodynamic preference for the complex, with the relative reaction free energy (ΔΔGoreaction = 32.93 kcal mol-1) representing the difference in Gibbs free energy change between the formation of CuQ 1:1 and 1:2 complexes, confirming the higher stability of CuQ 1:2. The complex exhibits enhanced α-amylase inhibitory activity (IC50 = 133 µM) compared to free quercetin (IC50 = 450 µM). The apparent IC50 value is reported alongside acarbose (IC50 = 148 µM) under identical assay conditions. These findings indicate that the coordination of Q with Cu(II) enhances the inhibitory activity of the α-amylase enzyme.